Exploring Research Trends in Sustainable Mountain and Rural Tourism (SMRT): A Bibliometric Study with Biblioshiny and VOS viewer - Ajay Bisht; Vipan Kumar; Ashish Nag; Suman Sharma; Rohit Thakur (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Mountain and rural tourism constitute significant segments of the global tourism industry, offering unique natural, cultural, and recreational experiences. This study presents a bibliometric analysis of sustainable mountain and rural tourism literature from 1990 to 2025, drawing on Scopus-indexed articles and utilising tools such as VOSviewer and Biblioshiny to identify key research themes, influential authors, and geographic trends. Major contributor countries include China, Spain, the United Kingdom, and Italy. Emerging topics cover socioeconomic empowerment, gender dynamics, rural population changes, and tourism development, with an emphasis on balancing economic growth and environmental conservation. The rise in demand, partly fuelled by increased health awareness and urban stress, underscores the importance of sustainable approaches that integrate community participation, policy innovation, and environmental stewardship. This synthesis highlights the critical role of mountain and rural tourism in fostering resilient economies and ecosystems while preserving cultural heritage, offering a roadmap for future research and sustainable development strategies.